2003
DOI: 10.1093/milmed/168.6.442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Static Stretching on Prevention of Injuries for Military Recruits

Abstract: This prospective study was designed to evaluate whether static stretching can prevent training-related injuries in Japan Ground Self-Defense Force military recruits. A total of 901 recruits between 1996 and 1998 were divided into two groups. Of which, 518 recruits were assigned to the stretching group and practiced static stretching before and after each physical training session. The control subjects (383 recruits in the nonstretching group) did not stretch statically prior to exercise. The static stretching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
17

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 0 publications
3
74
0
17
Order By: Relevance
“…One study reported a benefit of stretching for ankle sprains (McKay et al 2001); however, this was a retrospective survey study, and 4 randomized controlled trials have shown no benefits of stretching on the rates of ankle sprains (Amako et al 2003;Pope et al 1998Pope et al , 2000van Mechelen et al 1993).…”
Section: All-cause Injury Rate Vs Specific Injury Ratesmentioning
confidence: 94%
“…One study reported a benefit of stretching for ankle sprains (McKay et al 2001); however, this was a retrospective survey study, and 4 randomized controlled trials have shown no benefits of stretching on the rates of ankle sprains (Amako et al 2003;Pope et al 1998Pope et al , 2000van Mechelen et al 1993).…”
Section: All-cause Injury Rate Vs Specific Injury Ratesmentioning
confidence: 94%
“…The causes of musculoskeletal injuries result from a complex interaction of multiple risk factors and events [2]. Range of motion (ROM) has been known as one of the risk factors for increased musculoskeletal injuries [3,4]. Musculoskeletal flexibility is defined as the ability to move a joint through its complete ROM, and therefore it is important to maintain flexibility as decreased ROM is a contributing risk factor for injuries [5].…”
Section: Introduction *mentioning
confidence: 99%
“…Reviews have shown that stretching can mcrease flexibility (Smith CA, 1994), and that stretching is beneficial in reducing sprain and strain injuries (Smith RB, 1990). But others have shown no association with lower injury rates (Shier, 1999;Amako et al, 2003;Weldon et al, 2003;Pope et al, 2000) or that stretching was detrimental (Shier 1,1999) and Ho well DW (1984) showed a negative correlation between stretching and low back pain incidence in lightweight women rowers.…”
Section: Discussionmentioning
confidence: 99%